20 Direct reprogramming fibroblasts into endothelial cells. Issue 20 (23rd September 2011) - Margariti, A; Winkler, B; Karamariti, E; Tsai, T; Zeng, L; Hu, Y; Xu, Q
Abstract : The generation of induced pluripotent stem (iPS) cells is a fascinated tool for regenerative medicine. However, the main restriction for iPS cell application is a risk of tumour development. In this study we established a new method to generate a partially induced stem (PiPS) cells by transferring four reprogramming factors (OCT4, SOX2, KLF4 and c-MYC) to human fibroblasts. PiPS cells did not form tumours in vivo, and have abilities to specifically differentiate into different cell lineages, such as neurons, adipocytes, osteocytes, chondrocytes as well as endothelial cells in response to define media and culture conditions. The PiPS-derived endothelial cells expressed a panel of endothelial markers at gene and protein levels and they formed vascular tubes in vitro and in vivo Matrigel plaque assays. To clarify the mechanism of PiPS cell differentiation into endothelial lineage, data from a series of experiments indicate a novel gene SETSIP was crucial in endothelial differentiation. SETSIP was expressed in parallel with endothelial genes, and its overexpression induced endothelial marker expression, while its downregulation by shRNA resulted in suppression of these genes. Interesting, this protein was translocated to the cell nucleus during endothelial differentiation, while ChIP assays showed that it bound direct to VE-cadherin promoter. Functionally, PiPS-derived endothelial cells displayed clearly endothelial properties in two animal models. When seeded on decellularised vessels in a special constructed bioreactor and implanted in SCID mice, the cells displayed well attachment, stabilisation, patency and typical vascular structure. Also, these cells showed endothelial engraftment to form typical vascular architecture when they were injected into the infarcted tissues in an ischaemia model. Thus, we developed a new method to generate PiPS cells from human fibroblasts that can differentiate into a variety of cell types without tumour risk, in which endothelial cells can be produced via OCT4-VEGF-SETSIP pathway useful for regenerating damaged tissue and vessels in vivo.